Wnt inhibition induces persistent increases in intrinsic stiffness of human trabecular meshwork cells. (March 2015) - Morgan, Joshua T.; Raghunathan, Vijay Krishna; Chang, Yow-Ren; Murphy, Christopher J.; Russell, Paul
Abstract: Wnt antagonism has been linked to glaucoma and intraocular pressure regulation, as has increased stiffness of human trabecular meshwork (HTM) tissue. We have shown culturing HTM cells on substrates that mimic the elevated stiffness of glaucomatous tissue leads to elevated expression of the Wnt antagonist secreted frizzled related protein 1 (SFRP1), suggesting a linkage between SFRP1 and HTM mechanobiology. In this study, we document biomechanical consequences of Wnt antagonism on HTM cells. Cells were treated with the Wnt antagonists (SFRP1, KY02111, and LGK-974) for 8 days and allowed to recover for 4 days. After recovery, intrinsic cell stiffness and activation of the Wnt pathway via β-catenin staining and blotting were assayed. Basal cell stiffness values were 3.71 ± 0.37, 4.33 ± 3.07, and 3.07 ± kPa (median ± S.D.) for cells derived from 3 donors. Cell stiffness increased after 0.25 μg/mL (4.32 ± 5.12, 8.86 ± 8.51, 4.84 ± 3.15 kPa) and 0.5 μg/mL (16.75 ± 5.59, 13.18 ± 7.99, and 8.54 ± 5.77 kPa) SFRP1 treatment. Stiffening was observed after 10 μM KY02111 (10.72 ± 5.63 and 6.57 ± 5.53 kPa) as well as LGK-974 (9.60 ± 7.41 and 11.40 ± 9.24 kPa) treatment compared with controls (3.79 ± 1.01 and 5.16 ± 2.14 kPa). Additionally, Wnt inhibition resulted in decreased β-catenin staining and increased phosphorylation at threonine 41 after recovery. In conclusion, this work demonstrates a causal relationship between Wnt inhibition and cell stiffening. Additionally, these findings suggest transient Wnt inhibition resulted in durable modulation of the mechanical phenotype of HTM cells. When placed in context with previous results, these findings provide a causal link between Wnt antagonism and cell stiffness and suggest a feedback loop contributing to glaucoma progression. Highlights: We transiently exposed human trabecular meshwork (HTM) cells to Wnt antagonists. Atomic force microscopy (AFM) was used to measure HTM cell stiffness after recovery. Wnt antagonism resulted in long-term increases in HTM cell stiffness. This was accompanied by decreased β-catentin staining and increased phosphorylation.